Kepemilikan Manajerial Terhadap Kinerja Keuangan PT Indofood Sukses Makmur Pada Bursa Efek Indonesia - Alya Aulia Abdillah; Amalia Amalia; Fadillah Siva Azzahra; Natalya Puspawangi Nurhanifah; Ujang Suherman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
PT Indofood Sukses Makmur is a public company listed on the Indonesia Stock Exchange. One factor that can influence a company's financial performance is managerial ownership. The aim is to provide a holistic understanding of the relationship between managerial ownership interacting with the financial performance of a company and understand the factors that may or may limit the impact. The descriptive method for analyzing managerial ownership of the financial performance of PT Indofood Sukses Makmur on the Indonesia Stock Exchange can involve calculating certain formulas below. managerial ownership (km)(Number of managerial ownership shares)/(Number of outstanding shares) X 100%. Based on the results of the calculations above regarding managerial ownership in 2022 at PT. Indofood Sukses Makmur Tbk, namely the number of managerial ownership shares is 1,380,020 and the number of outstanding shares is 8,780,426,500, so the result of the number of managerial ownership shares and the number of outstanding shares is 0.00015717. The discussion regarding managerial ownership of financial performance includes an analysis of the impact of managerial share ownership by management on the company's financial performance. Conclusion regarding managerial ownership at PT Indofood Sukses Makmur can have a positive impact on the company's financial performance.